Aplikasi Game Edukasi ABC Space Typing menggunakan Godot Engine - Ahmad Daniaji Rosyiid; Elkana Lewi Santoso; Irfan Ramadhani (CAHAYAtech, 2020)
Computer subjects have their own appeal for elementary school students. Elementary school students are interested in computers because it is new to them. But in teaching and learning activities they are only interested in drawing and playing. In the typing lesson section, only a few students are interested in learning to type. Therefore, the teacher needs a more interesting way to provoke students' interest to be willing to type. This method is to invite students to play games with the educational elements of typing. This research was made using the GDLC method, game development begins with the initiation of a game model, pre-production with game planning and design, production by starting game coding, alpha version for the first test, beta version for the second test conducted by players, and version release, namely the form finished games that are ready to be played, which aims so that the system can be easily developed. This research was made to build an educational game with an educational element of typing. The software used to build this game is the Godot engine with the gdscript programming language. With an attractive game display, it is hoped that students will be more interested in learning to type.